Climate and its impact on barley cultivation in Diyala province (Journal of the College of Basic Education, 2024)
The research dealt with the climate and its impact on the cultivation of the barley crop in Diyala Governorate, where climate is one of the natural factors that affect the activity of the agricultural crop. Therefore, the research problem came with a question?It is how the climate, its elements and phenomena affect agricultural crops, especially the barley crop in Diyala Province. The research hypothesis was that there is a relationship between climate change and the cultivation of barley, and through this hypothesis, choosing the best area for the growth of the barley crop, from the climatic conditions suitable for growing the crop in the governorate. The research touched on the climatic requirements in the region for growing the crop in the governorate, which included the upper thermal limits, the lower and optimal limits, solar radiation, as well as the requirements for rain, humidity, and wind. The study showed that there is a relationship between climate elements and the requirements for growing barley Through statistical analysis, multiple correlation and multiple coefficient of determination were used. As for geographic information systems technology, which identified the best suitable areas for barley cultivation, they are located in the north and northeast, and therefore, due to the abundance of rain Due to the abundance of rain, which ranged between strong and moderate, including the districts of Kifri and Baladruz. The results of the statistical analysis showed the effect of climatic elements on the area and production of the barley crop, and that the most significant correlation was rain and wind, which reached a correlation value of (0.727). Likewise, wind speeds proved their statistical relationship with a strong, but inverse (negative) correlation value of (-0.807).